Critical Discursive Psychology - Parker, I. author. aut Link
XIV, 270 p.
Keywords: Critical Discursive Psychology addresses issues in critical discursive research in psychology, and outlines the historical context in the discipline for the emergence of qualitative debates. Key critical theoretical resources are described and assessed and a series of polemics is staged that brings together writers who have helped shape critical work in psychology. It also sets out methodological steps for critical readings of texts and arguments for the role of psychoanalytic theory in qualitative research.